2022
DOI: 10.1155/2022/6215573
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Metabolomics-Based Intervention of Yanghe Decoction on Hashimoto’s Thyroiditis

Abstract: Background. Yanghe decoction is a famous formula consisting of Rehmannia, deer horn gum, cinnamon, rue, Ephedra, ginger charcoal, and licorice. However, few studies have explored the role of the potential mechanism of Yanghe decoction in the treatment of Hashimoto’s thyroiditis by metabolomics. Methods. Nine mice were randomly divided into three groups: control group (group C), model group (group M), and drug administration group (group T), with three mice in each group. Mice in groups M and T were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In SLE, Amir Sharabi et al revealed that medicines for SLE affect the metabolism of T-cell subsets (including glycolysis, glutaminolysis, fatty acid, and glycosphingolipid metabolism), altering metabolite levels (33). Xing Zhang et al suggested that The levels of inflammatory factors and serum metabolites in mice with HT were changed after administration of Yanghe Decoctiont, indicating that Yanghe_Decoction reduces inflammatory factors in HT (12), while the metabolomic studies of HT after treatment are still absent in clinical.Consequently, we analyzed the serum metabolites of patients with HT in different clinical stages. LPC 18:0 sn-1, PC 38:6, SM 34:2, LPC 18:1 sn-1, and SM 36:2 were increased in both HTE and HTE groups compared to the control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In SLE, Amir Sharabi et al revealed that medicines for SLE affect the metabolism of T-cell subsets (including glycolysis, glutaminolysis, fatty acid, and glycosphingolipid metabolism), altering metabolite levels (33). Xing Zhang et al suggested that The levels of inflammatory factors and serum metabolites in mice with HT were changed after administration of Yanghe Decoctiont, indicating that Yanghe_Decoction reduces inflammatory factors in HT (12), while the metabolomic studies of HT after treatment are still absent in clinical.Consequently, we analyzed the serum metabolites of patients with HT in different clinical stages. LPC 18:0 sn-1, PC 38:6, SM 34:2, LPC 18:1 sn-1, and SM 36:2 were increased in both HTE and HTE groups compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Meantime, Chng et al found that antithyroid drug treatment increased the arginine levels during the transition from hyperthyroidism to euthyroidism in GD patients (11). Xing Zhang et al found that metabolic network and inflammatory factors were influenced and cured by Yanghe decoction in HT (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al found that polyamine metabolites showed different levels in serum between patients with thyroid disease (GD, pTab, HTS, HT) and healthy controls [10] . Meantime, the concentration of metabolic in serum can be also affected by treatment [14][15] .…”
Section: Introductionmentioning
confidence: 99%